Influence of KRAS activation in the colorectal cancer immunosurveillance escape - Machado, Ana Luísa (2018)
The immune system as a host defense system watches the cell growth and division, eliminating cells with antigens different from those present in healthy cells. However, some transformed cells have the capacity, through various mechanisms, to escape the immune system. Genomic instability and some mutations are pointed as possible mechanisms supporting the immunosurveillance escape, as is the case of KRAS mutation. This oncogenic mutation is present in about 30% of cases of colorectal cancer and confers to the tumor a greater potential for malignancy. It is known that KRAS mutant cancer cells regulate the recruitment, activation, and differentiation of immune cells, promoting tumor evolution by ensuring leakage to the immune system and increasing the proliferative potential. Few evidence highlights an association between a KRAS mutation and myeloid cells, mainly macrophages and neutrophils infiltration. However, the mechanism which determines this interaction remains unclear. Due to the growing knowledge of different immunosuppressive molecules, it became interesting to investigate if there is an alteration in these molecules related to the KRAS activation.